CONDUCTING VOCABULARY WORK WITH PRESCHOOL CHILDREN - Rimbayeva Ozoda Bazarbayevna (International Journal of Economic Integration and Regional Competitiveness, 2024)
conducting dictionary work with preschool children is an important task. The main task of dictionary work is: to enrich, expand and activate the dictionary Reserve. This article will talk about the work of raising the vocabulary of preschool children and the importance of this, provide information about the organization of vocabulary work and the tools used in the training process